2011
DOI: 10.1016/j.ijgo.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of retained placenta with acupuncture

Abstract: References[1] Hnat MD, Sibai BM, Caritis S, Hauth J, Lindheimer MD, MacPherson C, et al. Perinatal outcome in women with recurrent preeclampsia compared with women who develop preeclampsia as nulliparas. Am J Obstet Gynecol 2002;186(3):422-6. [2] Odendaal HJ, Pattinson RC, Bam R, Grove D, Kotze TJ. Aggressive or expectant management for patients with severe preeclampsia between 28-34 weeks' gestation: a randomized controlled trial. Obstet Gynecol 1990;76(6):1070-5. [3] Sibai BM, Mercer BM, Schiff E, Friedman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Clinical acupuncture has been recommended for the management of retained placentas, 23 and a 2012 study demonstrated the effectiveness of acupuncture for expulsion of retained placentas. 24 However, these studies were done when the placenta was retained one hour after birth, they used more than one acupuncture point, and none of the studies used the Ren Mai 6 acupuncture point.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical acupuncture has been recommended for the management of retained placentas, 23 and a 2012 study demonstrated the effectiveness of acupuncture for expulsion of retained placentas. 24 However, these studies were done when the placenta was retained one hour after birth, they used more than one acupuncture point, and none of the studies used the Ren Mai 6 acupuncture point.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent case report described the successful use of acupuncture at KI16 for retained placenta, highlighting its continued use as a non-invasive nonpharmacological method of third stage management. 21 The potential benefits of acupuncture include a reduced rate of manual removal of the placenta, which would be expected to lead to fewer complications such as early postpartum haemorrhage, uterine atony, uterine rupture, puerperal infection, anaemia and adverse side effects of anaesthesia. 21 22 These are potentially serious complications that can prolong recovery time in the early postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Its principal advantage would be avoiding manual exploration and complications associated with such a procedure, such as early postpartum hemorrhage, uterine atony, uterine rupture, puerperal infection, anemia, and adverse side-effects of anesthesia. 49 Despite the evidence presented above, rigorous randomized studies, particularly those using objective measures, have failed to identify any obvious benefits from acupuncture for many of the other conditions studied. 50 Acupuncture during labor and delivery is well-tolerated by patients and by medical staff members and practitioners who provide acupuncture delivery.…”
Section: Retained Placentamentioning
confidence: 99%